Complex networks & their applications V : proceedings of the 5th International Workshop on Complex Networks and their Applications (COMPLEX NETWORKS 2016) - Cherifi, Hocine; Gaito, Sabrina; Quattrociocchi, Walter; Sala, Alessandra (Springer, 2017)
This book highlights cutting-edge research in the field of network science, offering scientists, researchers and graduate students a unique opportunity to catch up on the latest advances in theory and a multitude of applications. It presents the peer-reviewed proceedings of the fifth International Workshop on Complex Networks & their Applications (COMPLEX NETWORKS 2016), which took place in Milan during the last week of November 2016. The carefully selected papers are divided into 11 sections reflecting the diversity and richness of research areas in the field. More specifically, the following topics are covered: Network models; Network measures; Community structure; Network dynamics; Diffusion, epidemics and spreading processes; Resilience and control; Network visualization; Social and political networks; Networks in finance and economics; Biological and ecological networks; and Network analysis.
International conference proceedings.
Includes author index.
Keywords: Computer networks -- Congresses.; Internet -- Congresses.; elektronické knihy; electronic books